Association between age-related macular degeneration and 25(OH) vitamin D levels in the Turkish population - Kabataş,Naciye (2022)
ABSTRACT Purpose: Age-related macular degeneration is the most common cause of blindness in developed countries, and several factors have been attributed for its etiology. This study was conducted to explore the relationship between serum vitamin D levels and age-related macular degeneration. Methods: We retrospectively analyzed the data of 114 patients with age-related macular degeneration. A total of 102 patients who did not have any other diseases than refractive error were allocated to the control group. The best-corrected visual acuity, fundus findings, and spectral domain optical coherence tomography findings were analyzed. Patients were allocated to groups based on the Age-related Eye Disease Study classification. Serum 25(OH) vitamin D levels were measured. The central foveal thickness and the subfoveal choroidal thickness were measured by optical coherence tomography. Results: The 25(OH) vitamin D levels in age- and gender-matched patients with age-related macular degeneration and in healthy subjects were 14.6 ± 9.8 and 29.14 ± 15.1 ng/ml, respectively. The age-related macular degeneration group had significantly lower vitamin D levels than the control group (p>0.001). The subfoveal choroidal thickness was lower in patients with age-related macular degeneration (p>0.001). The 25(OH) vitamin D level showed a weak positive correlation with choroidal thickness (r=0.357, p=0.01). When the level of 25(OH) vitamin D was evaluated according to the stages of age-related macular degeneration, it was found to be lower in the advanced-stage disease (p=0.01). The risk for the development of choroid neovascular membrane and subretinal fibrosis was found to increase with decreased vitamin D levels. Conclusions: Significantly decreased levels of 25(OH) vitamin D in advanced-stage age-related macular degeneration suggest a significant correlation existing between vitamin D deficiency and age-related macular degeneration development. Further studies are required to examine whether vitamin D supplementation has an effect on the development and progression of age-related macular degeneration.